Vertical‐cavity surface‐emitting lasers with birefringence splitting above 250 GHz. Issue 20 (1st October 2015) - Pusch, T.; Lindemann, M.; Gerhardt, N.C.; Hofmann, M.R.; Michalzik, R.
Abstract : Using the elasto‐optic effect, increase of the frequency difference between the two orthogonally polarised modes, the so‐called birefringence splitting, in standard single‐mode oxide‐confined AlGaAs‐based vertical‐cavity surface‐emitting lasers is achieved to values beyond 250 GHz. A large birefringence is required for the generation of ultra‐fast polarisation oscillations for potential future high‐speed communication applications.